Modelling Firm and Market Dynamics - A Flexible Model Reproducing Existing Stylized Facts - Thomas Brenner; Matthias Duschl (Philipps-University Marburg, Department of Geography, 2014)
This paper presents a firm and market model that is able to reproduce the empirically observed patterns on firm growth and its statistical characteristics. It goes beyond the existing firm models by reproducing all stylized facts established in the literature. Furthermore, the model is flexible so that it can be adapted to certain industries and life-cycle stages. We analyse and discuss the options that are provided by the various parameters in this sense.
Keywords: L11; L13; L22; L25; O12; C15; 330; Firm model; firm growth; market model; industry dynamics